Five-year analysis of isolated pathogens and antibiotic resistance of ocular infections from two large tertiary comprehensive hospitals in east China - Pan-Pan Li; Li Li; Jun-Fang Zhang; Bai Qin; Li-Hua Kang; Min Ji; Huai-Jin Guan (International Journal of Ophthalmology, 2024)
AIM: To analyze the spectrum of isolated pathogens and antibiotic resistance for ocular infections within 5y at two tertiary hospitals in east China. METHODS: Ocular specimen data were collected from January 2019 to October 2023. The pathogen spectrum and positive culture rate for different infection location, such as keratitis, endophthalmitis, and periocular infections, along with antibiotic resistance were analyzed. RESULTS: We included 2727 specimens, including 827 (30.33%) positive cultures. A total of 871 strains were isolated, 530 (60.85%) bacterial and 341 (39.15%) fungal strains were isolated. Gram-positive cocci (GPC) were the most common ocular pathogens. The most common bacterial isolates were Staphylococcus epidermidis (25.03%), Staphylococcus aureus (7.46%), Streptococcus pneumoniae (4.59%), Corynebacterium macginleyi (3.44%), and Pseudomonas aeruginosa (3.33%). The most common fungal genera were Fusarium spp. (12.74%), Aspergillus spp. (6.54%), and Scedosporium spp. (5.74%). Staphylococcus epidermidis strains showed more than 50% resistance to fluoroquinolones. Streptococcus pneumoniae and Corynebacterium macginleyi showed more than 90% resistance to erythromycin. The percentage of bacteria showing multidrug resistance (MDR) significantly decreased (χ2=17.44, P=0.002). CONCLUSION: GPC are the most common ocular pathogens. Corynebacterium macginleyi, as the fourth common bacterium, may currently be the local microbiological feature of east China. Fusarium spp. is the most common fungus. More than 50% of the GPC are resistant to fluoroquinolones, penicillins, and macrolides. However, the proportion of MDR strains has been reduced over time.